Goodbye Germany - und dann? Erste Ergebnisse einer Pilotstudie zur Befragung von Auswanderern aus Deutschland - Marcel Erlinghagen; Tim Stegmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
In contrast to the vast body of data on immigration to Germany, there is almost no scientifically valid data available on emigration flows from Germany and the factors motivating people to emigrate. In particular, there is an almost total lack of data on the living conditions of emigrants after their arrival in their new home countries. It is thus unsurpising that the German emigration research is currently based mainly on aggregated emigration data from official statistical sources as well as on non-representative quantitative and qualitative studies of specific emigrant groups. This was the point of departure for the pilot project "Life outside Germany" which attempted to follow Socio-Economic Panel Study (SOEP) participants who left Germany between 2002 and 2006, with the central aim of obtaining information about these individuals' motivations for leaving and their living conditions in their new home countries. The project succeeded in locating 67 of the 288 former SOEP respondents who had been identified as emigrants. These individuals were sent thespecially designed questionnaire by mail, and a total of 32 interviews were completed and returned. The present study starts by presenting the empirical findings from the pilot study. The main problem of the analysis lies less in the (controllable) selectivity of the respondents (32 of 288), and more the (still) extremely low case numbers, which do not allow scientifically sound conclusions to be drawn from the results. A further aim of this paper is therefore to provide an example of the basic research potential that lies in emigrant surveys, particularly in surveying SOEP respondents who have moved abroad. Linking information before and after the point of emigration creates new possibilities for empirical life-course research, which in turn - from an understanding of migration as a fundamentally open-ended process - open up new empirical perspectives for migration research.
Keywords: C81; F22; J61; 330; SOEP; migration; emigration; emigrants; Germany